Proposta de metodologia para diagnóstico, mensuração e contabilização de passivos ambientais - Andrade , Marcos (2017)
The study aimed to develop a methodology for the diagnosis, measurement, accounting and disclosure of environmental liabilities, analyzing the constraints present in the process. Faced with the scarcity of methodologies that could help Accounting in relation to environmental liabilities, the following problem arose: Is it possible to develop a methodology to diagnose, measure and account for environmental liabilities? The methodology used was the systematization of environmental infractions, to fit the insertion in the developed tool. The result obtained was an intuitive methodology that allows access to the environmental infractions foreseen in the national legislation and their respective monetary fines, indicating the form proposed by the accounting norm to measure, to account and to show these environmental liabilities. The conclusion of the study is that it is possible to develop a methodology through the systematization of environmental legislation, as well as this methodology can evolve into the form of application for mobile phones.